Investigating Factors Associating with Online Shoping Behavior on TikTok Live Streaming in Generation Z - Salomo Chandra Gupta Winarno; Bernardinus Harnadi; Berta Bekti Retnawati (SISFORMA, 2024)
TikTok is an application that is currently very popular with the public. This research aims to study the behavior of users/consumers from Generation Z in using the live streaming feature on TikTok which leads to the desire and interest in making online purchases/shopping. The research was carried out using a purposive sampling method and collected data from 300 respondents from Generation Z. The research analysis was directed at the correlation between factors and the technology acceptance factors studied to gain insight regarding the activity of using live streaming technology on TikTok for online shopping activities. The expected output from this research is factors that influence the acceptance of live streaming technology on TikTok for online shopping activities among Generation Z and the correlation between these factors and acceptance factors. The output of this research will help uncover the factors causing the increase in the use of the live streaming feature on TikTok in attracting online shopping interest from Generation Z. The elements found can be helpful for business people, online shopping consumers, and parties interested in increasing shopping interest online which is caused by the availability of technological features added to social media applications.